2020
DOI: 10.11591/ijpeds.v11.i1.pp64-74
|View full text |Cite
|
Sign up to set email alerts
|

Torque ripples improvement of direct torque controlled five-phase induction motor drive using backstepping control

Abstract: The paper proposes Direct Torque Control (DTC) of a five-phase induction motor drive with reduced torque ripple. The method presented here is the DTC Backstepping based on the classic DTC working with a constant switching frequency of the inverter. Another remarkable aspect is the complexity of the method proposed, both in the control unit of the inverter and in the number of correctors necessary for the control of the torque. The selection table and hysteresis have been eliminated. This method significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The aim of this strategy was to convert the nonlinear system into the linear system by involving some of the algebraically transformation. On the other hand, the combination of DTC control and non-linear control was also developed in multiphase named as backstepping control in [89].…”
Section: Intelligent/digital Controlmentioning
confidence: 99%
“…The aim of this strategy was to convert the nonlinear system into the linear system by involving some of the algebraically transformation. On the other hand, the combination of DTC control and non-linear control was also developed in multiphase named as backstepping control in [89].…”
Section: Intelligent/digital Controlmentioning
confidence: 99%
“…Numerous methods have been employed to detect the different types of faults in an IM [2][3][4][5]. These [6][7][8][9][10] apply to the current spectrum, vibration analysis, and other techniques to detect the different faults in the motors. Another study reported the impacts of motor and simulated motors, which were examined using motor current signature analysis (MCSA) and also through observation of magnetic flux density outside the motor [11].…”
Section: Introductionmentioning
confidence: 99%
“…Extended Kalman filter EKF has been proposed in [21] as a solution for better flux estimation. These approaches contain some inherent disadvantages such as highly computational processes [20], (v) artificial intelligent (AI) methods like artificial neural networks (ANNs) and fuzzy logic (FL) [22]- [24]. These techniques have a great attention in the last decades in many fields especially pattern recognition and control systems since they can deal with the complex or non-linear process without the needing for the relations between the input and output [25].…”
Section: Introductionmentioning
confidence: 99%